2016
DOI: 10.1016/j.jtcvs.2016.07.073
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after first-onset arrhythmia in Fontan physiology

Abstract: The development of an arrhythmia is associated with a heightened risk of subsequent failure of the Fontan circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…HLHS patients are estimated to require more resources on average as expected, and so are male children which is in line with the pediatric healthcare literature on gender 15 and previous Fontan studies. 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HLHS patients are estimated to require more resources on average as expected, and so are male children which is in line with the pediatric healthcare literature on gender 15 and previous Fontan studies. 16 …”
Section: Discussionmentioning
confidence: 99%
“…These conditions are not currently recognized as one of the most common noncardiac inpatient needs for this population, although a few previous studies [15][16][17][18] have reported worse dental caries experience and comorbidities in digestive system for children with heart disease. However, it is unclear from this study whether these admissions simply reflect more inpatient needs for this population on commonly seen conditions due to anesthesia concerns or that these children indeed had worse dental and digestive outcomes.…”
mentioning
confidence: 98%
“…Two-thirds of pacing for bradycardia is for sinus node dysfunction [213,214], as junctional rhythm is poorly tolerated and chronotropic incompetence significantly reduces exercise tolerance. The sinus node may have been damaged at the time of the prior superior vena cava-pulmonary artery anastomosis and is more common after the atriopulmonary Fontan procedure [215].…”
Section: Pacingmentioning
confidence: 99%
“…Delayed fenestration closure has become an integral part of Fontan surgery in many centres 8 9. The arrhythmic load of this population increases as they age and it is no surprise that a total of 122 patients needed a pacemaker implantation and 47 an ablation procedure 10 11. Ablation procedures have been shown to be successful in this population, but often requires multiple reinterventions 11 12.…”
Section: Discussionmentioning
confidence: 99%